Money Demand in Malaysia: Further Empirical Evidence - Huzaimi, Hussain; Liew, Venus Khim-Sen (IUP Publications, 2006)
A cointegration, error correction models and CUSUM stability test are employed in this study aimed at analyzing the money demand in Malaysia with relations to its determinants namely real income level, real interest rate, nominal exchange rate and the degree of monetization. Using Malaysian monthly data covering 1979M1 to 2002M5 we are able to find cointegration relationships among M1 as well as M2 and their determinants. CUSUM stability test shows that both M1 and M2 are stable in this sample period albeit the Financial Innovations and Liberalization and also Asia Financial Crisis. A key contribution of this study is the inclusion of the degree of monetization variable, which is found playing a the significant role in the cointegrating equation. Earlier studies that found no cointegration between money demand and its determinants in Malaysia – rendering Bank Negara Malaysia to shift its monetary targeting to interest rate targeting – may be due to the omission of the degree of monetization variable. Hence, this finding suggests that M1 and M2 can be effective monetary targeting tools in implementing monetary policy.